KERJASAMA ORANGTUA DAN GURU UNTUK MENGATASI KESULITAN BELAJAR SISWA KELAS 1 SEKOLAH DASAR - Cahcha Ferawati; Tri Wera Agrita; Tri Wiyoko (Jurnal Muara Pendidikan, 2023)
Learning difficulties usually appear in students who are characterized by low learning outcomes. Learning difficulties are a disorder in children related to cooperation. This research aims to reveal the cooperation between parents and teachers in efforts to overcome the learning difficulties of grade 1 students at SDN 37/II Pasar Lubuk Landai. This research uses a qualitative approach. The subjects of this research were 10 people consisting of school principals, teachers, parents, and students. The data collection techniques used in this research were interviews, questionnaires, and documentation. The analysis technique used is qualitative research data, namely data reduction, data presentation, and verification or making conclusions. The results of this research show that the collaboration between parents and teachers to overcome the learning difficulties of grade 1 students at SDN 37/II Pasar Lubuk Landai, has problems that occur for parents and teachers, and some problems occur for students, namely: (1) There is cooperation between parents and teachers in overcoming students' learning difficulties, namely communication via WhatsApp chat groups, parental participation in resolving student learning problems and parental participation in resolving student learning problems and parental participation in strengthening school provisions. (2) The obstacles faced by parents and teachers in teaching are intelligence, interest, talent, maturity, and readiness.